Crowdfunding as an Innovative Financial Policy Tool for SMEs: An Overview of the European Market - Werbowa, Oleksandra; Ziobrowska-Sztuczka, Justyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: The research is focused on an overview and evaluation of the potential of crowdfunding in the financial policy of small and medium enterprises (SMEs), paying particular attention to the European market, including varying forms and types which depend on the funding method, rewards in return, and how it is taxed and reported.Research Design & Methods: The study contains a review of crowdfunding based on investigations conducted by international organisations, as well as the analysis of the legal framework of crowdfunding platforms in EU regulations. A comparative analysis was conducted to highlight an overview of 663 crowdfunding platforms across 41 states, taking into account type, industry, rewards in return, and taxation and reporting processes. Based on data from selected crowdfunding platforms the authors present the most successful crowdfunding campaigns in 2022.Findings: Online alternative finance is gaining ground in finance policies of SMEs. There is a consensus among European legislative bodies that crowdfunding should be encouraged as a modern form of financing for the SME sector. However, in comparison to other developed economies, the EU crowdfunding market is underdeveloped. The authors highlighted the key features of the best crowdfunding campaigns in 2022. The Polish market strongly reflects the success of the various crowdfunding models.Implications / Recommendations: The obtained results seem to become a benchmark for reducing risks as well as ensuring diversification and stability in the financial policy of SMEs.Contribution: The issues discussed in the paper fill a research and methodological gap in research on crowdfunding as a way of financing SMEs.